Peran Mediasi Organizational Commitment Pada Pengaruh Work Environment Terhadap Employee Performance Pada Karyawan PT. Asuka Engineering Indonesia - Nadiya Nurkholifa; Budiono Budiono (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This research aims to test and explain the impact of the work environment on employee performance through organizational commitment as a mediator variable. The approach adopted in this study method used in this study is quantitative. The sampling technique used a saturated sample with an entire quantity of 50 employees. Data on this research were analyzed using Partial Least Square (PLS) with SmartPLS 3.0. software on the computer. The outcomes revealed a significant positive relationship between work environment and organizational commitment on employee performance. The result concludes that organizational commitment mediates the influence of work environment on employee performance, the result found that the work environment. The implication of this research is to obtain empirical evidence about the factors that influence employee performance, such as work environment and organizational commitment. The company can improve the work environment and organizational commitment to get higher employee welfare and impact the company to achieve its goals.